PELATIHAN BISNIS DIGITAL UNTUK GENERASI Z: MEMANFAATKAN MEDIA SOSIAL SEBAGAI PELUANG USAHA BAGI SISWA SLTA - Walhidayat, Walhidayat; Sadar, Muhamad; Putra, Septiandi; Syahtriatna, Syahtriatna (Fakultas Ilmu Komputer, 2025)
This community service activity aimed to enhance students’ understanding of social media content management for digital entrepreneurship at SMA PGRI Pekanbaru. The 8-hour workshop involved 50 selected students and focused on three key areas: content planning, social media algorithm optimization, and content performance analysis. Evaluation using questionnaires and quizzes showed a significant improvement of 82.5% in participants’ understanding. Specifically, the ability to create content schedules increased from 25% to 89%, strategic hashtag usage from 18% to 76%, and content insight analysis from 12% to 68%. Additionally, 73% of students could create a one-week content calendar, and 65% identified optimal posting times based on audience analysis. The learning-by-doing approach through business account simulations proved effective. Main challenges included limited student perspectives and varying levels of digital literacy. Solutions included self-study modules and group division based on skill levels. The program recommends integrating social media content management into school entrepreneurship curricula with continuous practice and periodic evaluation.